Cross bones - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2005)
The latest gripping thriller from world class forensic anthropologist, Kathy Reichs, bestselling author of Bare Bones and Monday Mourning Temperance Brennan has a mystifying new case in this eighth novel from New York Times bestselling author and world-class forensic anthropologist Kathy Reichs. Tempe is called in to interpret the wounds of a man who was shot in the head, but while she tries to make sense of the fracture patterning, an unknown man slips her a photograph of a skeleton, telling her it holds the answer to the victim's death. Detective Andrew Ryan is also on the case and, as his relationship with Tempe heats up, together they try to figure out who this orthodox Jew in the Israeli "import business" really was. Was he involved in the black market trade in antiquities? And what is the significance of the photo? With the help of Jacob Drum, a biblical archaeologist and old friend from the University of North Carolina, Tempe follows the trail of clues all the way to Israel. In the Holy Land, she learns of a strange ossuary at Masada, a shroud, and a tomb that may have held the remains of Jesus's family. But the further she probes into the identity of the ancient skeleton, the more she seems to be putting herself in danger...